Impact of vaccine against peste-des-petits ruminants (PPR) in India: An analysis using economic surplus model - BARDHAN, D; SINGH, R P; KUMAR, SANJAY; ANANDASEKARAN, G; MERAJ, MOHD (The Indian Journal of Animal Sciences, 2017)
Peste-des-Petits Ruminants (PPR) as an acute contagious disease in sheep and goats has proved costly and is considered as one of the most important health constraints in rearing of small ruminants. ICAR-Indian Veterinary Research Institute, Izatnagar had developed a vaccine against the disease through research project during the period 1997-2001. The vaccine has been marketed by various agencies, both public and private since 2007-08 in many states of the country. The economic feasibility of PPR control programme using the above vaccine at the national level was estimated using an economic surplus model. The change in total economic surplus and research and delivery cost were projected from 1997 (year of the start of the research project) to 2030 (by which 100% of small ruminant population is to be vaccinated, as per OIE/FAO specifications) after adjusting for the above adoption pattern. The benefits to society (economic surplus) and costs of control programme were deflated using a suitable consumer price index to 2016 level. Using a long run discount rate of 7.5%, the benefits were compared to researchand delivery cost and the NPV, IRR and BCR were calculated. The change in total surplus as a result of vaccination of sheep and goats against PPR was ₹ 8,253 crore per annum. The study revealed that the vaccination programme resulted into significant economic benefits (NPV= ₹ 489 crore). The IRR and BCR were 119% and 123:1, respectively. Sensitivity analysis revealed that the benefits were most sensitive to higher assumption of discount rate and lower assumption of degree of immunity provided by the vaccine accounting for uncertainties in the efficacy of the vaccine at the field level. In both the case, the net benefits decreased significantly. Net benefits to society also significantly decreased upon the assumption of declining adoption rates and ceiling adoption not reaching 100% level.